Collaborative Culture in Higher Education Institutions in Pokhara - Resam Lal Poudel; Umesh Singh Yadav (Pravaha, 2024)
This study investigated collaborative culture (CC) among faculty in Nepalese higher education institutions (HEIs), aiming to understand the discrepancy between espoused values and actual collaborative practices. Employing a mixed-methods approach, quantitative data from 236 faculty members across eight HEIs in Pokhara and qualitative insights from focus group discussions revealed a complex picture. While faculty valued diversity, trust, and teamwork, the study identified key challenges hindering effective collaborative culture implementation. These included political interference in institutional affairs, negative perceptions and experiences with teamwork, and diversity practices that were often formalistic and lacked genuine integration. The study indicated that while collaborative culture is recognized as essential, its practical realization is hampered by these political and cultural factors. Bridging the gap between policy and practice requires policy reforms that promote inclusive collaboration, active faculty engagement in collaborative initiatives, and institutional leadership that models and champions collaborative behavior.